Dancing on the sun stone : Mexican women and the gendered politics of Octavio Paz - Becker, Marjorie, 1952-; Project Muse. (Albuquerque : University of New Mexico Press, 2022)
"Dancing on the Sun Stone is a uniquely transdisciplinary work that fuses modern Latin American history and literature to explore women's lives and gendered politics in Mexico. In this important work, scholar Marjorie Becker focuses on the complex Mexican women of rural Michoacán who performed an illicit revolutionary dance and places it in dialogue with Nobel Prize winner Octavio Paz's signature poem, 'Sun Stone'--allowing a new gendered history to emerge. Through this dialogue, the women reveal intimate and intellectual complexities of Mexican women's gendered voices, their histories, and their intimate and public lives. Dancing on the Sun Stone further demonstrates the ways these women, in dialogue with Paz, transformed history itself. Becker's multigenre work reconstructs Mexican history through the temporal experiences of crucial Michoacán females, experiences that culminate in their complex revolutionary dance, which itself emerges as a transformative revolutionary language. The book also explores Mexican artists Rosario Castellanos and Alfonson Cuarón, each of whom provides alternative approaches to Mexico's gendered temporality and each of whom speaks to the Mexico the Michoacán dancers imagined and embodied. Becker illustrates how the work of both the artists and the dancers seeks a world where women experience equality, safety, and recognition" --
Acknowledgments -- Introduction -- Walking into history : when women made tortillas, danced, and reconfigured time -- From killing stone to gendered time-scape : Octavio Paz and the making of the "Sun Stone" -- Dancing on the sun stone -- The dance of Paz's legacy -- Coda : Dancing with the dancers.
Includes bibliographical references and index.
Marjorie Becker is an associate professor of history and English at the University of Southern California.
Print version record.
eBooks on EBSCOhost
Keywords: Paz, Octavio, -- 1914-1998. -- Criticism and interpretation; Piedra de sol (Paz, Octavio); Women -- Mexico -- Michoacán de Ocampo -- Social conditions; Women revolutionaries -- Mexico -- History; Sex role -- Mexico -- Michoacán de Ocampo -- History; Mexico -- History -- 1910-1946.; Femmes -- Mexique -- Michoacán (État) -- Conditions sociales; Femmes révolutionnaires -- Mexique -- Histoire; Rôle selon le sexe -- Mexique -- Michoacán (État) -- Histoire; Mexique -- Histoire -- 1910-1946.; Sex role; Women revolutionaries; Women -- Social conditions; Mexico; Mexico -- Michoacán de Ocampo; 1910-1946; Criticism, interpretation, etc; History